Effect of chromium compounds on synthesis of alkali metal ferrates (VI) - Головко, Дмитрий Аркадьевич (Eastern-European Journal of Enterprise Technologies, 2015)
The process features of producing alkali metal ferrates (VI) in the presence of chromium and its compounds, which are contained in the feedstock were investigated. It was found that during the ferrate synthesis, chromium impurities move from iron components to the alkaline solution and crystalline ferrates as oxoanion CrO42. It is shown that at long-term storage of crystalline ferrates and their solutions in the presence of chromates, their decomposition degree increases. The influence of chromium impurities on the synthesis effectiveness of ferrate solutions by various methods was determined. It was revealed that during transpassive electrochemical dissolution with increasing chromium content in the anode material > 0.8%, a decrease in the target product yield is observed. Technological solutions to minimize the accumulation of Cr (VI) compounds in the target product, which lie in a rational feedstock selection, as well as the obligatory inclusion of several crystallization and extraction stages in inorganic (KOH solutions) and organic (methanol) solvents to the production cycle were proposed.